lo g ( tan 1 ∘ ) + lo g ( tan 2 ∘ ) + lo g ( tan 3 ∘ ) + … + lo g ( tan 8 9 ∘ ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We know that lo g ( m ) + lo g ( n ) = lo g ( m n ) and, tan θ = cot θ 1 .
Using the concepts above, it is easy to see that lo g ( tan ( 1 ) ) + . . . lo g ( tan ( 8 9 ) ) reduces to tan 4 5 .
The value of tan 4 5 is 1 and we know that lo g ( 1 ) to the base anything is always 0 .
Hence, the answer is 0 .
Log1 base 1is not zero
log tan 1 + log tan 2 + log tan 3 + ....................+ log tan 89 = log ( tan 1 x tan 2 x tan 3 x .............. x tan 89) = log { (tan 1 x tan 89) x (tan 2 x tan 88) x ( tan 3 x tan 87) x ................ x (tan 44 x tan 46) x tan 45} = log { ( tan 1 x tan (90 - 1) ) x ( tan 2 x tan ( 90 -2)) x ( tan 3 x tan (90 - 3)) x ............x ( tan 44 x tan (90 - 44)) x tan 45 } = log { (tan 1 x cot 1) x ( tan 2 x cot 2 ) x ( tan 3 x cot 3) x ......x( tan 44 x cot 44 ) x tan 45 } = log { 1 x 1 x 1 x .....................x 1 x tan 45} = log { tan 45} = log 1 = 0
good ..nice explanaion sir
We know t a n ( x ) = s i n ( x ) / c o s ( x )
so:
l o g ( t a n ( x ) ) = l o g ( s i n ( x ) ) − l o g ( c o s ( x ) )
We also know that c o s ( x ) = s i n ( 9 0 ∘ − x ) . This means:
l o g ( t a n ( 1 ∘ ) ) + . . . + l o g ( t a n ( 8 9 ∘ ) ) = l o g ( s i n ( 1 ∘ ) ) + . . . + l o g ( s i n ( 8 9 ∘ ) ) − l o g ( c o s ( 1 ∘ ) ) − . . . − l o g ( c o s ( 8 9 ∘ ) = l o g ( s i n ( 1 ∘ ) ) + . . . + l o g ( s i n ( 8 9 ∘ ) ) − l o g ( s i n ( 8 9 ∘ ) ) − . . . − l o g ( s i n ( 1 ∘ ) ) = 0
log(tan1)+log(tan2)+tan(tan3)+......+log(tan89)=log(tan1.tan2.tan3....tan89)
=log1
=0
Applied Excel for both addition and multiplication to confirm.
Log 1 = 0
In fact, (Tan x)(Cot x) = 1 for (Pi/ 2 - x) swap between Sin x and Cos x within the range.
n = 1 ∑ 8 9 lo g tan n ° = lo g n = 1 ∏ 8 9 tan n °
tan 1 ° × tan 8 9 ° = tan 1 ° cot 1 ° = 1
Similarly every term cancels out except tan 4 5 ° = 1
So, finally: n = 1 ∑ 8 9 lo g tan n ° = lo g n = 1 ∏ 8 9 tan n ° = lo g 1 = 0
log(tan1)+log(tan2)+log(tan3)+...+log(tan88)+log(tan89)=(log(tan1)+log(tan89))+(log(tan2)+log(tan88))+...+(log(tan49)+log(tan41)) we have log(a)+log(b)=log(a b)=> log(tan1)+log(tan89)=log(tan1 tan89), we also have tan(1) tan(89)=sin(1) sin(89)/cos(1) cos(89) =(cos(88)-cos(90))/(cos(90)+cos(88))=1 => log(tan1)+log(tan89)=log(tan1 tan89)=log(1)=0 so the total is 0
tan(1) tan(89) = 1, tan(2) tan(88) = 1, ...
we can simplify to log(1) = 0
The sum: lo g ( tan 1 ∘ ) + lo g ( tan 2 ∘ ) + lo g ( tan 3 ∘ ) + … + lo g ( tan 8 9 ∘ ) could be expressed as lo g ( ( tan 1 ∘ ) x ( tan 2 ∘ ) x ( tan 3 ∘ ) x … x ( tan 8 9 ∘ ) ) Which is equal to lo g ( x = 1 ∏ 8 9 tan x ) We can derive that tan 1 ∘ x tan 8 9 ∘ = tan 2 ∘ x tan 8 8 ∘ = tan 4 5 ∘ = 1 etc . So ( x = 1 ∏ 8 9 tan x ) = 1 ∴ lo g ( x = 1 ∏ 8 9 tan x ) = lo g 1 = 0
note that tan1.tan2.tan3.............tan89 is 1 since tan1=tan89=cot1 & tanxcotx=1 so tan1.tan2.tan3...........tan89 = tan1.tan89.tan.tan2..........tan44.tan46.tan45=1.1.1.1......tan45 = tan45=1 so log(tan1.tan2.tan3..........tan45)=log(1)=0 (since 10^0=1) so answer is 0
Firstly, let a=log(tan1°)+log(tan2°)+log(tan3°)+..+log(tan89°).
Then from log(x)+log(y)= log(xy), we obtain that
a=log[(tan1°)(tan2°)(tan3°)...(tan89°)].
Also from tan(x-y)=(tanx-tany)/(tanx-tany) and tan(90°)=∞, we can verify that
tan(90°-x)=1/tan(x). Thus, that we get a= log[(tan1°)(tan2°)...(tan44°)(tan45°)tan(90°-46°)...tan(90°-1°)] a=log[(tan1°)(tan2°)(tan3°)...(tan44°)(1)(1/tan44°)...(1/tan3°)(1/tan2°)(1/tan1°)] a=log(1) ∴a=0.
Problem Loading...
Note Loading...
Set Loading...
First, we gather all the terms into a single logarithm: lo g ( tan 1 ° ) + lo g ( tan 2 ° ) + ⋯ + lo g ( tan 8 9 ° ) = lo g ( tan 1 ° × tan 2 ° × ⋯ × tan 8 9 ° )
Then we observe that, because of symmetry of the sine and cosine functions, tan 1 ° = tan 8 9 ° 1 , tan 2 ° = tan 8 8 ° 1 and so on.
In this way, we have tan 1 ° × tan 8 9 ° = tan 2 ° × tan 8 8 ° = tan 4 5 ° = 1 .
Then, we get that: lo g ( tan 1 ° × tan 2 ° × ⋯ × tan 8 9 ° ) = lo g ( 1 × 1 × ⋯ × 1 ) = lo g ( 1 ) = 0